Assessment of the minimum value of photovoltaic electricity in Italy. Issue 2 (10th June 2014) - Pagliaro, Mario; Meneguzzo, Francesco; Zabini, Federica; Ciriminna, Rosaria
Abstract We investigate the value of solar photovoltaic (PV) power in the Italian wholesale electricity market (IPEX). A model is developed and applied to simulate and predict the monthly average electricity prices in peak hours, as well as to simulate scenarios without PV generation. The computed merit‐order effect of the PV generation in Italy, around −2.9 €/MWh per each additional GWh of PV production, as well as the greater −4.5 €/MWh absolute value evaluated under the hypothesis of stationary electricity demand, are in line with the upper values found in related studies of near mature renewable energy markets. A strong relationship of the value of PV electricity in the IPEX with the electricity demand is clearly evident, leading to important policy implications in terms of possible actions on the granted subsidies, electrification of energy end use, and promotion of specific PV technologies. The anomalous temporal behavior of the IPEX, shown by high off‐peak electricity prices that followed the installation of Italy's large PV park, partly offsets the beneficial effect of PV generation.